EVALUATING THE TRIAD OF ECONOMIC DRIVERS: HOUSEHOLD CONSUMPTION, INVESTMENT, AND GOVERNMENT EXPENDITURE IN INDONESIA'S GROWTH TRAJECTORY (2016-2024) – AN ISLAMIC ECONOMICS PERSPECTIVE - Syaichoni, Ahmad; Hidayati, Amalia Nuril; Elrani, Igfira Mailana; Anggraini, Sisilia (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study analyzes the influence of household consumption, investment, and government spending on Indonesia's economic growth from 2016 to 2024, by integrating an Islamic economic perspective. Quarterly secondary data from the Central Statistics Agency and the Financial Services Authority are used in multiple linear regression analysis, which is validated through classical assumption tests. The results show that household consumption and government spending have a positive and significant effect on economic growth, in line with Keynesian theory. However, investments, measured through Islamic mutual funds, show negative impacts, contrary to conventional economic expectations. This phenomenon is caused by the dominance of non-productive financial instruments, such as money market and fixed income mutual funds, which divert funds from productive sectors such as infrastructure and MSMEs. From the perspective of Islamic economics, these findings underscore the importance of investments that are not only sharia-compliant but also productive and socially beneficial, as emphasized by Umer Chapra in the concept of ethical and equitable growth. The research also underscores the crucial role of household consumption, supported by government stimulus during the COVID-19 pandemic, in maintaining Indonesia's economic resilience. Therefore, policy reforms are needed to improve the efficiency of government spending and direct investment to sectors that support long-term growth. By incorporating Islamic principles, this research offers a new approach to understanding Indonesia's economic dynamics, contributing to the literature on development economics and Islamic finance. These findings provide valuable insights for policymakers to design balanced economic strategies, which not only drive growth but also social well-being.